Konseptualisasi Bahasa Al-Quran Perspektif Muhammad Arkoun Sebagai Interpretasi terhadap Realitas Kehidupan Modern - syafrinal syaf; Muhammad Ghazali Siregar; Nabil Makarim; Sahroni Nasution (Universitas Islam Negeri Imam Bonjol Padang, 2024)
This paper examines the transformation of the reading and meaning of the Qur'an by actualizing it in the existing reality. The research method in this paper is exploratory descriptive research, in explanatory research, it is research that aims to describe or describe clearly the problems studied. Exploratory is a method that functions to deepen intellectual studies or to get new ideas about a problem being studied. Arkoun was one of the Islamic thinkers who came from al-Jazair but was heavily influenced by French thought, by collaborating with new ideas in studying Islam, especially in rereading the Qur'an in terms of linguistics and meaning. By looking at the readings that have been done previously, Arkoun assesses that there is a lot of mystical and there are some meanings that are missing from various readings that put the Qur'an into a narrow realm and the readings carried out only focus on a few studies such as theology, Sufism and filth, but also must touch the social conditions according to the conditions of the current reality. Therefore, there is a need for a rereading or transformation of meaning by looking at the new reality and epistemology in interpreting the Qur'an.